Lithium source additive, lithium iron phosphate positive electrode material and preparation method and application of lithium iron phosphate positive electrode material
By adding dopamine-covered lithium source additives to the lithium iron phosphate positive electrode material, the problems of insufficient electrolyte wetting and lithium ion diffusion ability of the high-pressure positive electrode of lithium iron phosphate are solved, and the energy density and electrochemical performance of the battery are improved.
Patent Information
- Application Number
- CN202411802191.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
AI Technical Summary
The lithium iron phosphate high-pressure positive electrode exhibits reduced electrolyte wetting and diffusion ability of lithium ions in lithium-ion batteries, limiting its performance in high-performance applications. In addition, the formation of the SEI film on the graphite negative electrode consumes active lithium, resulting in a low Coulomb efficiency for the first cycle, which reduces the capacity and energy density of the lithium-ion power battery.
By adding dopamine-covered lithium source additives to the preparation raw materials of lithium iron phosphate positive electrode material, the active lithium source is increased, and the active lithium consumed by the SEI film on the surface of the negative electrode graphite is made up, and pores are made during the battery formation process, thereby improving the porosity of the positive electrode sheet and the wetting ability of the electrolyte.
The gram capacity of lithium iron phosphate positive electrode material and the electrolyte infiltration rate are improved, the energy density and electrochemical kinetic performance of the battery are improved, and the first-effect and capacity retention rate of the battery are enhanced.
Smart Images

Figure CN119627079A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium source additive, a lithium iron phosphate positive electrode material, and a preparation method and application thereof. Background Art
[0002] Lithium iron phosphate (LiFePO4, LFP for short) cathode material has been widely used in the field of lithium-ion batteries due to its high safety, long cycle life and low cost. In order to improve the energy density of the battery, it is usually necessary to subject the lithium iron phosphate cathode material to high-pressure compaction treatment. However, the high-pressure compaction process has high requirements on the particle size, morphology and distribution of the material, and the preparation process is relatively complicated. With the development of technology and the increase in application needs, the high-pressure compaction cathode of lithium iron phosphate has also exposed several shortcomings. Among them, the high-pressure compaction cathode significantly reduces the wettability of the electrolyte and inhibits the diffusion ability of lithium ions. This shortcoming limits its performance in certain high-performance applications.
[0003] In addition, the organic electrolyte will be reduced and decomposed on the surface of negative electrodes such as graphite to form a solid electrolyte interface (SEI) film, which consumes lithium from the positive electrode, resulting in a low coulombic efficiency (ICE) of the first cycle, reducing the capacity of the lithium-ion power battery and thus affecting the energy density.
[0004] Therefore, how to ensure the structural stability of the high-density lithium iron phosphate positive electrode, increase the electrolyte infiltration ability, and compensate for the consumption of active lithium ions due to the formation of SEI on the graphite surface is an urgent problem that needs to be solved in the current high-energy density lithium iron phosphate battery market for further promotion and application.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] One of the purposes of the present invention is to provide a lithium source additive, the lithium source additive comprising a lithium source and a dopamine layer covering the surface of the lithium source. The present invention prepares a lithium source additive by covering the surface of the lithium source with dopamine, thereby increasing the active lithium source and compensating for the active lithium consumed by the film formation on the negative electrode graphite surface.
[0007] The second purpose of the present invention is to provide a method for preparing the lithium source additive.
[0008] The third object of the present invention is to provide a lithium iron phosphate positive electrode material, wherein the raw materials for preparing the lithium iron phosphate positive electrode material include an iron source, a phosphorus source, a lithium source, a carbon source and the lithium source additive. The present invention increases the active lithium source by adding a dopamine-covered lithium source additive to the lithium iron phosphate positive electrode material, thereby compensating for the active lithium consumed by the film formation on the negative electrode graphite surface, and at the same time, during the battery formation process, pores are formed in the lithium iron phosphate positive electrode sheet, thereby increasing the porosity of the positive electrode sheet and improving the wetting ability of the electrolyte.
[0009] A fourth object of the present invention is to provide a method for preparing the lithium iron phosphate positive electrode material.
[0010] A fifth object of the present invention is to provide an application of the lithium source additive or the lithium iron phosphate positive electrode material in the preparation of a lithium ion battery.
[0011] A sixth object of the present invention is to provide a positive electrode plate for a lithium-ion battery.
[0012] A seventh object of the present invention is to provide a lithium ion battery.
[0013] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0014] In a first aspect, the present invention provides a lithium source additive, comprising a lithium source and a dopamine layer covering a surface of the lithium source.
[0015] Preferably, the lithium source is selected from lithium oxalate and / or lithium squarate.
[0016] Preferably, the mass of the dopamine layer accounts for 0.05-0.5% of the total mass of the lithium source additive.
[0017] In a second aspect, the present invention provides a method for preparing the lithium source additive as described in the first aspect, wherein the method for preparing the lithium source additive comprises the following steps:
[0018] Dissolving lithium salt, acid and dopamine hydrochloride in water respectively to prepare lithium salt solution, acid solution and dopamine hydrochloride solution;
[0019] The lithium salt solution and the acid solution are mixed, reacted, and then filtered to obtain a lithium source;
[0020] The lithium source and dopamine hydrochloride solution are mixed, stirred, filtered, washed and dried to obtain the lithium source additive.
[0021] Preferably, the molar ratio of the lithium salt to the acid is 1:(0.8-1.2).
[0022] Preferably, the lithium salt is selected from lithium carbonate.
[0023] Preferably, the acid is selected from oxalic acid and / or squaric acid.
[0024] Preferably, the step of mixing the lithium salt solution and the acid solution is specifically: adding the acid solution into the lithium salt solution under stirring.
[0025] Preferably, during the mixing of the lithium salt solution and the acid solution, the stirring speed is 100 to 1000 rpm, and the speed of adding the lithium salt solution is controlled at 2 to 10 mL / min.
[0026] Preferably, the reaction time is 20 to 40 minutes.
[0027] Preferably, the mass ratio of the lithium source to dopamine hydrochloride is 1:(0.005-0.05).
[0028] Preferably, during the mixing of the lithium source and the dopamine hydrochloride solution, the stirring speed is 100 to 1000 rpm and the stirring time is 3 to 10 minutes.
[0029] In a third aspect, the present invention provides a lithium iron phosphate positive electrode material, wherein raw materials for preparing the lithium iron phosphate positive electrode material include an iron source, a phosphorus source, a lithium source, a carbon source and the lithium source additive as described in the first aspect.
[0030] Preferably, the molar ratio of the iron source, phosphorus source, lithium source and carbon source is 1:(0.8-1.2):(0.8-1.2):(0.1-0.3).
[0031] Preferably, the amount of the lithium source additive added is 0.1-1% of the total mass of the raw materials for preparing the lithium iron phosphate positive electrode material.
[0032] In a fourth aspect, the present invention provides a method for preparing the lithium iron phosphate positive electrode material, the preparation method comprising the following steps:
[0033] The iron source, the phosphorus source, the lithium source and the carbon source are mixed and ground for the first time to obtain a primary mixed material;
[0034] The mixed material and the lithium source additive are mixed and pre-sintered to obtain a pre-sintered material;
[0035] Grinding the pre-sintered material for a second time to obtain a secondary mixed material;
[0036] sintering the secondary mixed material to obtain a sintered material;
[0037] The sintered material is crushed and then sieved to obtain the lithium iron phosphate positive electrode material.
[0038] Preferably, the rotation speed of the first grinding is 100-500 rpm, and the time of the first grinding is 20-40 min.
[0039] Preferably, the pre-sintering process is performed in an air atmosphere.
[0040] Preferably, the heating rate of the pre-sintering treatment is 1-10 / min, the temperature of the pre-sintering treatment is 550-650°C, and the time of the pre-sintering treatment is 1-3h.
[0041] Preferably, the rotation speed of the second grinding is 200-1000 rpm, and the time of the second grinding is 20-40 min.
[0042] Preferably, the sintering process is performed under a methane atmosphere.
[0043] Preferably, the heating rate of the sintering process is 1-10 / min, the temperature of the sintering process is 650-750°C, and the time of the sintering process is 10-15h.
[0044] Preferably, the pulverization treatment is carried out by ball milling, the ball-to-material ratio of the ball milling is (30-50):1, the rotation speed of the ball milling is 500-2000 rpm, and the ball milling time is 30-60 min.
[0045] Preferably, the mesh size of the sieving is 100 to 300 meshes.
[0046] In a fifth aspect, the present invention provides a use of the lithium source additive or the lithium iron phosphate positive electrode material in the preparation of a lithium ion battery.
[0047] In a sixth aspect, the present invention provides a lithium-ion battery positive electrode plate, wherein the lithium-ion battery positive electrode plate comprises the lithium iron phosphate positive electrode material.
[0048] In a seventh aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the lithium-ion battery positive electrode sheet as described in the sixth aspect.
[0049] Compared with the prior art, the present invention has the following beneficial effects:
[0050] (1) The present invention increases the active lithium source by adding a dopamine-covered lithium source additive to the raw materials for preparing lithium iron phosphate, thereby compensating for the active lithium consumed by the film formation on the negative electrode graphite surface; at the same time, during the battery formation process, the lithium iron phosphate positive electrode sheet is pore-formed, thereby increasing the porosity of the positive electrode sheet and improving the wetting ability of the electrolyte;
[0051] (2) The lithium iron phosphate positive electrode material of the present invention has better performance and a higher gram capacity of lithium iron phosphate; and the electrolyte infiltration rate of the positive electrode sheet after formation is faster;
[0052] (3) The lithium iron phosphate full battery assembled by the present invention has a higher initial efficiency and a higher capacity retention rate; and the assembled lithium iron phosphate full battery has a lower resistance, which improves the electrochemical kinetics of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0054] Figure 1 This is the SEM image of the lithium source additive provided in Example 1.
[0055] Figure 2 This is the XRD pattern of the lithium source additive provided in Example 1.
[0056] Figure 3 XRD diagram of the lithium iron phosphate positive electrode material provided in Example 1 and Comparative Example 1.
[0057] Figure 4 Cross-sectional view of the LFP positive electrode of the full cell assembled in Application Example 1.
[0058] Figure 5 The full battery cycle performance diagram assembled for Application Example 1 and Comparative Application Examples 1-2. DETAILED DESCRIPTION
[0059] Unless otherwise defined herein, scientific and technological terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.
[0060] It should be noted that specific details are described in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in a variety of other ways different from those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0061] The embodiments of the present invention will be described in detail below in conjunction with the embodiments and examples, but it will be appreciated by those skilled in the art that the following embodiments and examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified, proceed according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0062] In a first aspect, the present invention provides a lithium source additive, comprising a lithium source and a dopamine layer covering a surface of the lithium source.
[0063] In the present invention, the lithium source additive uses a lithium source covered with dopamine. In the preparation process of lithium iron phosphate positive electrode materials, the lithium source additive of this structure can increase the active lithium source and make up for the active lithium consumed by the film formation on the negative electrode graphite surface. At the same time, in the preparation process of lithium iron phosphate positive electrode materials, adding the lithium source additive of this structure can solve the problem of high compaction of lithium iron phosphate positive electrode and poor electrolyte infiltration ability, and can also reduce the pole piece impedance of the high compaction electrode of lithium iron phosphate positive electrode, and supplement the active lithium ions consumed by the formation of SEI on the graphite surface, thereby significantly improving the energy density of the battery.
[0064] In some optional embodiments, the lithium source is selected from lithium oxalate and / or lithium squarate.
[0065] In some optional embodiments, the mass of the dopamine layer accounts for 0.05-0.5% of the total mass of the lithium source additive, for example, it can be 0.05%, 0.06%, 0.08%, 0.1%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25%, 0.26%, 0.28%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, etc.
[0066] In a second aspect, the present invention provides a method for preparing the lithium source additive as described in the first aspect, wherein the method for preparing the lithium source additive comprises the following steps:
[0067] Dissolving lithium salt, acid and dopamine hydrochloride in water respectively to prepare lithium salt solution, acid solution and dopamine hydrochloride solution;
[0068] The lithium salt solution and the acid solution are mixed, reacted, and then filtered to obtain a lithium source;
[0069] The lithium source and dopamine hydrochloride solution are mixed, stirred, filtered, washed and dried to obtain the lithium source additive.
[0070] It should be noted that in the process of preparing the lithium source additive, the addition of dopamine hydrochloride solution has two functions: one is to adjust the pH, and the other is to cover the surface of the lithium source with a dopamine layer to facilitate subsequent carbonization to generate a nitrogen-doped carbon layer.
[0071] In some optional embodiments, the molar ratio of the lithium salt to the acid is 1:(0.8-1.2), for example, 1:0.8, 1:0.85, 1:0.9, 1:0.95, 1:0.98, 1:1, 1:1.02, 1:1.05, 1:1.1, 1:1.15, 1:1.2, etc.
[0072] In some optional embodiments, the lithium salt is selected from lithium carbonate.
[0073] In some optional embodiments, the acid is selected from oxalic acid and / or squaric acid.
[0074] When the lithium salt is selected from lithium carbonate and the acid is selected from oxalic acid, the reaction equation is:
[0075] Li2CO3+H2C2O4→Li2C2O4+CO2↑+H2O;
[0076] When the lithium salt is selected from lithium carbonate and the acid is selected from squaric acid, the reaction equation is:
[0077] Li2CO3+H2C4O4→Li2C4O4+CO2↑+H2O.
[0078] In some optional embodiments, the step of mixing the lithium salt solution and the acid solution is specifically: adding the acid solution to the lithium salt solution under stirring.
[0079] In some optional embodiments, the lithium source in the lithium source additive is prepared by the following steps: slowly adding the acid solution to the lithium salt solution under stirring; after the acid solution is added, continuing to stir to obtain a reaction mixture; filtering the reaction mixture, collecting the precipitate, and obtaining the lithium source.
[0080] It should be noted that during the reaction of the lithium salt and the acid, the acid solution needs to be added slowly under stirring conditions in order to ensure that the reaction proceeds evenly. At the same time, after the acid solution is added, stirring must be continued to ensure that the reaction is complete.
[0081] In some optional embodiments, during the mixing of the lithium salt solution and the acid solution, the stirring speed is 100 to 1000 rpm, for example, it can be 100 rpm, 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm, 1000 rpm, etc., and the speed of adding the lithium salt solution is controlled at 2 to 10 mL / min, for example, it can be 2 mL / min, 3 mL / min, 4 mL / min, 5 mL / min, 6 mL / min, 7 mL / min, 8 mL / min, 9 mL / min, 10 mL / min, etc.
[0082] In some optional embodiments, the reaction time is 20 to 40 min, for example, it can be 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, 32 min, 34 min, 36 min, 38 min, 40 min, etc.
[0083] In some optional embodiments, the mass ratio of the lithium source to dopamine hydrochloride is 1:(0.005-0.05), for example, it can be 1:0.005, 1:0.006, 1:0.008, 1:0.01, 1:0.012, 1:0.014, 1:0.015, 1:0.016, 1:0.018, 1:0.02, 1:0.022, 1:0.024, 1:0.025, 1:0.026, 1:0.028, 1:0.03, 1:0.035, 1:0.04, 1:0.045, 1:0.05, etc.
[0084] In some optional embodiments, during the mixing of the lithium source and dopamine hydrochloride solution, the stirring speed is 100-1000rpm, for example, it can be 100rpm, 200rpm, 300rpm, 400rpm, 500rpm, 600rpm, 700rpm, 800rpm, 900rpm, 1000rpm, etc., and the stirring time is 3-10min, for example, it can be 3min, 4min, 5min, 6min, 7min, 8min, 9min, 10min, etc.
[0085] In a third aspect, the present invention provides a lithium iron phosphate positive electrode material, wherein raw materials for preparing the lithium iron phosphate positive electrode material include an iron source, a phosphorus source, a lithium source, a carbon source and the lithium source additive as described in the first aspect.
[0086] In the present invention, during the preparation of the lithium iron phosphate positive electrode material, an active lithium source (the lithium source additive described in the first aspect) is added to make up for the active lithium consumed by the film formation on the negative electrode graphite surface. At the same time, during the battery formation process, holes are formed in the lithium iron phosphate positive electrode sheet to increase the porosity of the positive electrode sheet and improve the wetting ability of the electrolyte.
[0087] In some optional embodiments, the molar ratio of the iron source, phosphorus source, lithium source and carbon source is 1:(0.8-1.2):(0.8-1.2):(0.1-0.3);
[0088] Among them, the first "0.8~1.2" can be, for example, 0.8, 0.85, 0.9, 0.95, 1, 1.05, 1.1, 1.15, 1.2, etc.; among them, the second "0.8~1.2" can be, for example, 0.8, 0.85, 0.9, 0.95, 1, 1.05, 1.1, 1.15, 1.2, etc.; among them, "0.1~0.3" can be, for example, 0.1, 0.15, 0.2, 0.25, 0.3, etc.
[0089] In some optional embodiments, the amount of the lithium source additive added is 0.1% to 1% of the total mass of the raw materials for preparing the lithium iron phosphate positive electrode material, for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc.
[0090] In a fourth aspect, the present invention provides a method for preparing the lithium iron phosphate positive electrode material, the method for preparing the lithium iron phosphate positive electrode material comprising the following steps:
[0091] The iron source, the phosphorus source, the lithium source and the carbon source are mixed and ground for the first time to obtain a primary mixed material;
[0092] The mixed material and the lithium source additive are mixed and pre-sintered to obtain a pre-sintered material;
[0093] Grinding the pre-sintered material for a second time to obtain a secondary mixed material;
[0094] sintering the secondary mixed material to obtain a sintered material;
[0095] The sintered material is crushed and then sieved to obtain the lithium iron phosphate positive electrode material.
[0096] It should be noted that in the process of preparing the lithium iron phosphate positive electrode material of the present invention, the iron source, phosphorus source, lithium source and carbon source need to be mixed and then ground for the first time to ensure that the components are fully mixed; and a second grinding is required during the pre-sintering treatment to ensure the fineness and uniformity of the powder; further, crushing and sieving are required after the sintering treatment to ensure that the lithium iron phosphate powder with uniform particle size distribution is obtained.
[0097] In some optional embodiments, the rotation speed of the first grinding is 100-500 rpm, for example, it can be 100 rpm, 150 rpm, 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, etc.
[0098] In some optional embodiments, the first grinding time is 20 to 40 min, for example, it can be 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, 32 min, 34 min, 36 min, 38 min, 40 min, etc.
[0099] In some optional embodiments, the pre-sintering process is performed in an air atmosphere.
[0100] In some optional embodiments, the heating rate of the pre-sintering treatment is 1 to 10 / min, for example, 1 / min, 2 / min, 3 / min, 4 / min, 5 / min, 6 / min, 7 / min, 8 / min, 9 / min, 10 / min, etc.
[0101] In some optional embodiments, the temperature of the pre-sintering treatment is 550-650°C, for example, 550, 560, 570, 580, 590, 600, 610, 620, 630, 640, 650, etc.
[0102] In some optional embodiments, the pre-sintering treatment time is 1 to 3 hours, for example, it can be 1h, 1.2h, 1.4h, 1.5h, 1.6h, 1.8h, 2h, 2.2h, 2.4h, 2.5h, 2.6h, 2.8h, 3h, etc.
[0103] In some optional embodiments, the rotation speed of the second grinding is 200-1000 rpm, for example, it can be 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm, 1000 rpm, etc.
[0104] In some optional embodiments, the second grinding time is 20 to 40 min, for example, it can be 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, 32 min, 34 min, 36 min, 38 min, 40 min, etc.
[0105] In some optional embodiments, the sintering process is performed under a methane atmosphere.
[0106] In some optional embodiments, the heating rate of the sintering process is 1 to 10 / min, for example, it can be 1 / min, 2 / min, 3 / min, 4 / min, 5 / min, 6 / min, 7 / min, 8 / min, 9 / min, 10 / min, etc.
[0107] In some optional embodiments, the sintering temperature is 650-750°C, for example, 650, 660, 670, 680, 690, 700, 710, 720, 730, 740, 750°C, etc.
[0108] In some optional embodiments, the sintering treatment time is 10 to 15 hours, for example, it can be 10 hours, 10.5 hours, 11 hours, 11.5 hours, 12 hours, 12.5 hours, 13 hours, 13.5 hours, 14 hours, 14.5 hours, 15 hours, etc.
[0109] In some optional embodiments, the pulverization process is performed by ball milling.
[0110] In some optional embodiments, the ball-to-material ratio of the ball mill is (30-50):1, for example, it can be 30:1, 35:1, 40:1, 45:1, 50:1, etc.
[0111] In some optional embodiments, the rotation speed of the ball mill is 500-2000 rpm, for example, it can be 500 rpm, 600 rpm, 800 rpm, 1000 rpm, 1200 rpm, 1400 rpm, 1500 rpm, 1600 rpm, 1800 rpm, 2000 rpm, etc.
[0112] In some optional embodiments, the ball milling time is 30 to 60 min, for example, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, etc.
[0113] In some optional embodiments, the mesh size of the sieving is 100-300 mesh, for example, it can be 100 mesh, 120 mesh, 140 mesh, 160 mesh, 180 mesh, 200 mesh, 220 mesh, 240 mesh, 260 mesh, 280 mesh, 300 mesh, etc.
[0114] In a fifth aspect, the present invention provides a use of the lithium source additive or the lithium iron phosphate positive electrode material in the preparation of a lithium ion battery.
[0115] In a sixth aspect, the present invention provides a lithium-ion battery positive electrode plate, wherein the lithium-ion battery positive electrode plate comprises the lithium iron phosphate positive electrode material.
[0116] In some optional embodiments, the lithium-ion battery positive electrode plate further includes a binder, a conductive agent and a dispersant.
[0117] In some optional embodiments, the binder in the positive electrode plate is polyvinylidene fluoride (PVDF).
[0118] In some optional embodiments, the conductive agent in the positive electrode plate is conductive carbon black (SP).
[0119] In some optional embodiments, the dispersant in the positive electrode plate is a polyether silicone copolymer dispersant (BYK).
[0120] In a seventh aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the lithium-ion battery positive electrode sheet as described in the sixth aspect.
[0121] In some optional embodiments, the lithium-ion battery further includes a negative electrode sheet and an electrolyte.
[0122] In some optional embodiments, the negative electrode sheet includes a graphite main material, a binder, a conductive agent and a solvent.
[0123] In some optional embodiments, the main graphite material in the negative electrode sheet is ES2-A.
[0124] In some optional embodiments, the binder in the negative electrode sheet includes styrene-butadiene rubber latex (SBR) and / or carboxymethyl cellulose (CMC).
[0125] In some optional embodiments, the conductive agent in the negative electrode sheet is conductive carbon black (SP).
[0126] In some optional embodiments, the solvent in the negative electrode sheet is ethylene carbonate (EC) and / or 1,3-butanediol (SCH).
[0127] In some optional embodiments, the electrolyte includes a lithium salt and a solvent.
[0128] In some optional embodiments, the lithium salt in the electrolyte is LiPF6.
[0129] In some optional embodiments, the solvent in the electrolyte includes any one of ethylene carbonate (EC), ethyl methyl carbonate (EMC) or dimethyl carbonate (DMC) or a combination of at least two thereof.
[0130] The present invention is further described below by means of specific examples and comparative examples. However, it should be understood that these examples are only used for more detailed description and should not be construed as limiting the present invention in any form.
[0131] The raw material parameters in the following examples are as follows:
[0132]
[0133]
[0134] Example 1
[0135] This embodiment provides a lithium source additive and a lithium iron phosphate positive electrode material prepared by adding the lithium source additive.
[0136] 1. Preparation of lithium source additives:
[0137] (1) 7.39 g of Li2CO3 was dissolved in 100 mL of distilled water to prepare a Li2CO3 solution; 12.61 g of H2C2O4·2H2O was dissolved in 100 mL of distilled water to prepare a H2C2O4·2H2O solution; 0.2036 g of dopamine hydrochloride was dissolved in 100 mL of distilled water to prepare a dopamine hydrochloride solution;
[0138] (2) Under stirring conditions (200 rpm), slowly (10 mL / min) add the H2C2O4·2H2O solution to the Li2CO3 solution while maintaining stirring to ensure that the reaction proceeds evenly; lithium oxalate precipitate is generated during the reaction, and stirring is continued at 200 rpm for 30 min to ensure that the reaction is complete, and the reaction mixture is filtered to collect the precipitate to obtain lithium oxalate;
[0139] (3) adding the collected precipitate lithium oxalate to the dopamine hydrochloride solution, stirring at a speed of 500 rpm for 5 minutes, and then covering the surface of the lithium oxalate with a dopamine layer, and then filtering, washing and drying in sequence to obtain the lithium source additive (dopamine-coated lithium oxalate).
[0140] Figure 1 This is a SEM image of the lithium source additive provided in Example 1. Figure 1 As shown, it appears as fine crystalline particles with a smooth surface, and the particle size can range from 100nm to 5μm.
[0141] Figure 2 The XRD pattern of the lithium source additive provided in Example 1. Figure 2 As shown, the main characteristic peaks of the lithium source additive and lithium oxalate are highly overlapped, which means that the main component of the lithium source additive is lithium oxalate.
[0142] 2. Preparation of lithium iron phosphate positive electrode material:
[0143] (1) 15.97 g of Fe2O3, 11.50 g of NH4H2PO4, 7.39 g of Li2CO3 and 3.60 g of C6H 12 O6 was put into a grinder, mixed evenly, and ground at a speed of 500 rpm for 30 min to obtain a primary mixed material;
[0144] (2) The primary mixed material and 0.3 g of a lithium source additive (dopamine-coated lithium oxalate) were placed in a crucible, placed in a muffle furnace, and heated to 600° C. at a rate of 5 / min under air atmosphere, kept at that temperature for 2 h, and naturally cooled to room temperature to obtain a pre-sintered material;
[0145] (3) grinding the pre-sintered material again at a rotation speed of 500 rpm for 30 min to obtain a secondary mixed material;
[0146] (4) putting the secondary mixed material into a crucible, placing it in a muffle furnace, raising the temperature to 700°C at a rate of 5 / min under a methane protective atmosphere, keeping the temperature for 12 hours, and naturally cooling it to room temperature to obtain a sintered material;
[0147] (5) The sintered material was taken out, crushed by a ball mill (ball-to-material ratio of 30:1, rotation speed of 500 rpm, time of 60 min), and passed through a 200-mesh sieve to obtain lithium iron phosphate powder with uniform particle size distribution.
[0148] Example 2
[0149] This embodiment provides a lithium source additive and a lithium iron phosphate positive electrode material prepared by adding the lithium source additive.
[0150] 1. Preparation of lithium source additives:
[0151] (1) Dissolve 7.39 g of Li2CO3 in 100 mL of distilled water to prepare a Li2CO3 solution; dissolve 11.41 g of H2C4O4 in 100 mL of distilled water to prepare a H2C4O4 solution; dissolve 0.2036 g of dopamine hydrochloride in 100 mL of distilled water to prepare a dopamine hydrochloride solution;
[0152] (2) Under stirring conditions (200 rpm), slowly (10 mL / min) add the H2C4O4 solution to the Li2CO3 solution while maintaining stirring to ensure that the reaction proceeds evenly; lithium squarate precipitate is generated during the reaction, and stirring is continued at 200 rpm for 30 min to ensure that the reaction is complete, and the reaction mixture is filtered to collect the precipitate to obtain lithium squarate;
[0153] (3) adding the collected precipitate lithium squarate to the dopamine hydrochloride solution, stirring at a speed of 500 rpm for 5 minutes, and then covering the surface of the lithium squarate with a layer of dopamine, and then filtering, washing and drying in sequence to obtain the lithium source additive (dopamine-coated lithium squarate).
[0154] 2. Preparation of lithium iron phosphate positive electrode material:
[0155] (1) 15.97 g of Fe2O3, 11.50 g of NH4H2PO4, 7.39 g of Li2CO3 and 3.60 g of C6H 12 O6 was put into a grinder, mixed evenly, and ground at a speed of 500 rpm for 30 min to obtain a primary mixed material;
[0156] (2) The primary mixed material and 0.3 g of a lithium source additive (dopamine-coated lithium squarate) were placed in a crucible, placed in a muffle furnace, and heated to 600° C. at a rate of 5 / min under air atmosphere, kept at that temperature for 2 h, and naturally cooled to room temperature to obtain a pre-sintered material;
[0157] (3) grinding the pre-sintered material again at a rotation speed of 500 rpm for 30 min to obtain a secondary mixed material;
[0158] (4) putting the secondary mixed material into a crucible, placing it in a muffle furnace, raising the temperature to 700°C at a rate of 5 / min under a methane protective atmosphere, keeping the temperature for 12 hours, and naturally cooling it to room temperature to obtain a sintered material;
[0159] (5) The sintered material was taken out, crushed by a ball mill (ball-to-material ratio of 30:1, rotation speed of 500 rpm, time of 60 min), and passed through a 200-mesh sieve to obtain lithium iron phosphate powder with uniform particle size distribution.
[0160] Example 3
[0161] This embodiment provides a lithium source additive and a lithium iron phosphate positive electrode material prepared by adding the lithium source additive. The only difference from Example 1 is that in the preparation process of the lithium source additive, step (1) is adjusted to: dissolve 0.1 g of dopamine hydrochloride in 100 mL of distilled water to prepare a dopamine hydrochloride solution, and the other steps are exactly the same as Example 1.
[0162] Example 4
[0163] This embodiment provides a lithium source additive and a lithium iron phosphate positive electrode material prepared by adding the lithium source additive. The only difference from Example 1 is that in the preparation process of the lithium source additive, step (1) is adjusted to: dissolve 0.3 g of dopamine hydrochloride in 100 mL of distilled water to prepare a dopamine hydrochloride solution, and the other steps are exactly the same as Example 1.
[0164] Example 5
[0165] This embodiment provides a lithium source additive and a lithium iron phosphate positive electrode material prepared by adding the lithium source additive. The only difference from Example 1 is that during the preparation of the lithium iron phosphate positive electrode material, the content of the lithium source additive is adjusted to 0.2 g, and the other steps are exactly the same as Example 1.
[0166] Example 6
[0167] This embodiment provides a lithium source additive and a lithium iron phosphate positive electrode material prepared by adding the lithium source additive. The only difference from Example 1 is that during the preparation of the lithium iron phosphate positive electrode material, the content of the lithium source additive is adjusted to 0.4 g, and the other steps are exactly the same as Example 1.
[0168] Example 7
[0169] This embodiment provides a lithium source additive and a lithium iron phosphate positive electrode material prepared by adding the lithium source additive, which is different from the embodiment 1 only in that:
[0170] In the preparation process of lithium iron phosphate positive electrode material, the pre-sintering treatment in step (2) is adjusted as follows: in an air atmosphere, the temperature is raised to 550°C at a heating rate of 3 / min, kept at that temperature for 3 hours, and naturally cooled to room temperature to obtain a pre-sintered material;
[0171] In the preparation process of lithium iron phosphate positive electrode material, the pre-sintering treatment in step (4) is adjusted as follows: in a methane protective atmosphere, the temperature is raised to 650°C at a heating rate of 3 / min, kept at that temperature for 15 hours, and naturally cooled to room temperature to obtain a sintered material.
[0172] Example 8
[0173] This embodiment provides a lithium source additive and a lithium iron phosphate positive electrode material prepared by adding the lithium source additive, which is different from the embodiment 1 only in that:
[0174] In the preparation process of lithium iron phosphate positive electrode material, the pre-sintering treatment in step (2) is adjusted as follows: in an air atmosphere, the temperature is raised to 650°C at a heating rate of 7 / min, kept at that temperature for 1.5 hours, and naturally cooled to room temperature to obtain a pre-sintered material;
[0175] In the preparation process of lithium iron phosphate positive electrode material, the pre-sintering treatment in step (4) is adjusted as follows: in a methane protective atmosphere, the temperature is raised to 750°C at a heating rate of 7 / min, kept at that temperature for 10 hours, and naturally cooled to room temperature to obtain a sintered material.
[0176] Comparative Example 1
[0177] This comparative example provides a lithium iron phosphate positive electrode material, and the lithium iron phosphate positive electrode material is prepared by one step.
[0178] (1) 15.97 g of Fe2O3, 11.50 g of NH4H2PO4, 7.39 g of Li2CO3 and 3.60 g of C6H 12 O6 was put into a grinder, mixed evenly, and ground at a speed of 500 rpm for 30 min to obtain a primary mixed material;
[0179] (2) placing the primary mixed material into a crucible, placing it in a muffle furnace, heating it to 600°C at a rate of 5 / min in an air atmosphere, keeping the temperature for 2 h, and cooling it naturally to room temperature to obtain a pre-sintered material;
[0180] (3) grinding the pre-sintered material again at a rotation speed of 500 rpm for 30 min to obtain a secondary mixed material;
[0181] (4) putting the secondary mixed material into a crucible, placing it in a muffle furnace, raising the temperature to 700°C at a rate of 5 / min under a methane protective atmosphere, keeping the temperature for 12 hours, and naturally cooling it to room temperature to obtain a sintered material;
[0182] (5) The sintered material is taken out, crushed by a ball mill (ball-to-material ratio: 1, rotation speed: 500 rpm, time: 60 min), and passed through a 200-mesh sieve to obtain lithium iron phosphate powder with uniform particle size distribution.
[0183] Figure 3 XRD diagrams of lithium iron phosphate positive electrode materials provided for Example 1 and Comparative Example 1. From the comparison between Example 1 and Comparative Example, it can be seen that some small peaks other than LFP appear between 20 and 30°, which are characteristic peaks of the lithium source additive (lithium oxalate).
[0184] Comparative Example 2
[0185] This comparative example provides a lithium iron phosphate positive electrode material, which is different from Example 1 only in that, during the preparation of the lithium source additive, the dopamine hydrochloride solution is replaced with distilled water, and the other steps are completely consistent with Example 1.
[0186] Comparative Example 3
[0187] This comparative example provides a lithium iron phosphate positive electrode material, which differs from Example 1 only in that, in the preparation process of the lithium source additive, in step (1), the dopamine hydrochloride solution is replaced by a urea nitrogen source solution of equal concentration, and the other steps are exactly the same as Example 1.
[0188] Comparative Example 4
[0189] This comparative example provides a lithium iron phosphate positive electrode material, which differs from comparative example 1 only in that, during the preparation of the lithium source additive, lithium oxalate is replaced with lithium ferrite of equal mass, and the other steps are completely consistent with example 1.
[0190] Application Example 1
[0191] This application example provides a lithium iron phosphate battery, the lithium iron phosphate battery comprising:
[0192] Assembled battery: 5Ah lithium iron phosphate full battery;
[0193] Positive electrode sheet: 96.8wt% LFP (lithium iron phosphate positive electrode material provided in Example 1) + 1.78wt% PVDF (binder) + 1.2wt% SP (conductive agent) + 0.3wt% BYK (polyether silicone copolymer dispersant);
[0194] Negative electrode sheet: 95.7wt% ES2-A (graphite main material) + 1.8wt% SBR (binder) + 1.0wt% CMC (binder) + 1.5wt% SP (conductive agent) + 0.35wt% (EC+SCH);
[0195] Electrolyte: 1M LiPF6 electrolyte (the solvent consists of EC, EMC and DMC in a volume ratio of 1:1:1).
[0196] Figure 4 This is a cross-sectional view of the LFP positive electrode of the full battery assembled in Application Example 1. Figure 4 As shown, after the battery is formed, the lithium source additive and lithium iron phosphate are tightly combined, and some holes begin to appear in the middle of the lithium source additive, which is beneficial to the infiltration of the electrolyte.
[0197] Application Example 2
[0198] This application example provides a lithium iron phosphate battery, which differs from application example 1 only in that the lithium iron phosphate positive electrode material provided in example 1 is replaced with an equal amount of the lithium iron phosphate positive electrode material provided in example 2.
[0199] Application Example 3
[0200] This application example provides a lithium iron phosphate battery, which differs from application example 1 only in that the lithium iron phosphate positive electrode material provided in example 1 is replaced with an equal amount of the lithium iron phosphate positive electrode material provided in example 3.
[0201] Application Example 4
[0202] This application example provides a lithium iron phosphate battery, which differs from application example 1 only in that the lithium iron phosphate positive electrode material provided in example 1 is replaced with an equal amount of the lithium iron phosphate positive electrode material provided in example 4.
[0203] Application Example 5
[0204] This application example provides a lithium iron phosphate battery, which differs from application example 1 only in that the lithium iron phosphate positive electrode material provided in example 1 is replaced with an equal amount of the lithium iron phosphate positive electrode material provided in example 5.
[0205] Application Example 6
[0206] This application example provides a lithium iron phosphate battery, which differs from application example 1 only in that the lithium iron phosphate positive electrode material provided in example 1 is replaced with an equal amount of the lithium iron phosphate positive electrode material provided in example 6.
[0207] Application Example 7
[0208] This application example provides a lithium iron phosphate battery, which differs from application example 1 only in that the lithium iron phosphate positive electrode material provided in example 1 is replaced with an equal amount of the lithium iron phosphate positive electrode material provided in example 7.
[0209] Application Example 8
[0210] This application example provides a lithium iron phosphate battery, which differs from application example 1 only in that the lithium iron phosphate positive electrode material provided in example 1 is replaced with an equal amount of the lithium iron phosphate positive electrode material provided in example 8.
[0211] Comparative application example 1
[0212] This application example provides a lithium iron phosphate battery, which differs from application example 1 only in that the lithium iron phosphate positive electrode material provided in embodiment 1 is replaced with an equal amount of the lithium iron phosphate positive electrode material provided in comparative example 1.
[0213] Comparative Application Example 2
[0214] This application example provides a lithium iron phosphate battery, which differs from application example 1 only in that the lithium iron phosphate positive electrode material provided in embodiment 1 is replaced with an equal amount of the lithium iron phosphate positive electrode material provided in comparative example 2.
[0215] Comparative Application Example 3
[0216] This application example provides a lithium iron phosphate battery, which differs from application example 1 only in that the lithium iron phosphate positive electrode material provided in embodiment 1 is replaced with an equal amount of the lithium iron phosphate positive electrode material provided in comparative example 3.
[0217] Comparative Application Example 4
[0218] This application example provides a lithium iron phosphate battery, which differs from application example 1 only in that the lithium iron phosphate positive electrode material provided in embodiment 1 is replaced with an equal amount of the lithium iron phosphate positive electrode material provided in comparative example 4.
[0219] Test Case
[0220] Test samples: the lithium iron phosphate batteries provided in Application Examples 1 to 8 and the lithium iron phosphate batteries provided in Comparative Application Examples 1 to 4.
[0221] Test method:
[0222] (1) Capacity in grams:
[0223] At a temperature of 45°C, the assembled battery was charged to 4.2V at a rate of 0.1C, and the charge capacity Q1 of the battery was recorded. Formed gram capacity = charge capacity (mAh) / mass of active material (g).
[0224] (2) Full battery first effect:
[0225] At a temperature of 45°C, discharge the formed battery at a rate of 0.1C to 2.5V, and record the battery's discharge capacity Q2. The first efficiency of the full battery = Q1 / Q2.
[0226] (3) Resistance of the positive electrode after formation:
[0227] Disassemble the formed battery, keep the positive electrode, and use anhydrous ethanol or other suitable solvents to clean the surface of the electrode to remove dust and impurities on the surface. After drying, use the four-point probe method to test the resistance. The spacing between the four probes is consistent, with a spacing of 2mm. The current I is 0.1mA, and the voltage value U is recorded. The resistance R = U / I, record 6 points, and take the average value.
[0228] (4) Electrolyte immersion time after formation:
[0229] Disassemble the formed battery, keep the positive electrode, and use anhydrous ethanol or other suitable solvent to clean the surface of the electrode to remove dust and impurities on the surface. After drying, use a pipette to take 20 microliters of electrolyte and drop it on the surface of the electrode, cover the cuvette, and observe the time t(s) for the electrolyte to disappear.
[0230] The specific test results are shown in Table 1 and Table 2. Figure 5 As shown:
[0231] Table 1
[0232]
[0233] As shown in Table 1, the formation gram capacity of the lithium iron phosphate battery of the present invention reaches more than 167mAh / g, and the first efficiency of the whole battery reaches more than 94%; after the battery is formed, the resistance of the positive electrode plate is reduced to less than 53Ω, and the electrolyte infiltration time after formation is reduced to less than 152s. This fully illustrates that in the preparation process of the lithium iron phosphate positive electrode material, the present invention increases the active lithium source, supplements the active lithium ions consumed by the formation of SEI on the graphite surface, and improves the energy density of the battery; at the same time, in the battery formation process, the lithium iron phosphate positive electrode plate is pore-formed, and the porosity of the positive electrode plate is increased, thereby solving the problem of high compaction of the lithium iron phosphate positive electrode and poor electrolyte infiltration ability, and can also reduce the plate impedance of the high compaction electrode of the lithium iron phosphate positive electrode.
[0234] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A lithium source additive, characterized in that: The lithium source additive includes a lithium source and a dopamine layer covering the surface of the lithium source.
2. The lithium source additive according to claim 1, characterized in that: The lithium source is selected from lithium oxalate and / or lithium squarate; Preferably, the mass of the dopamine layer accounts for 0.05-0.5% of the total mass of the lithium source additive.
3. A method for preparing the lithium source additive according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: Dissolving lithium salt, acid and dopamine hydrochloride in water respectively to prepare lithium salt solution, acid solution and dopamine hydrochloride solution; The lithium salt solution and the acid solution are mixed, reacted, and then filtered to obtain a lithium source; The lithium source and dopamine hydrochloride solution are mixed, stirred, filtered, washed and dried to obtain the lithium source additive.
4. The method for preparing the lithium source additive according to claim 3, characterized in that: The molar ratio of the lithium salt to the acid is 1:(0.8-1.2); Preferably, the lithium salt is selected from lithium carbonate; Preferably, the acid is selected from oxalic acid and / or squaric acid; Preferably, the step of mixing the lithium salt solution and the acid solution is specifically: adding the acid solution to the lithium salt solution under stirring; Preferably, during the mixing of the lithium salt solution and the acid solution, the stirring speed is 100 to 1000 rpm, and the speed of adding the lithium salt solution is controlled at 2 to 10 mL / min; Preferably, the reaction time is 20 to 40 minutes; Preferably, the mass ratio of the lithium source to dopamine hydrochloride is 1:(0.005-0.05); Preferably, during the mixing of the lithium source and the dopamine hydrochloride solution, the stirring speed is 100 to 1000 rpm and the stirring time is 3 to 10 minutes.
5. A lithium iron phosphate positive electrode material, characterized in that: The raw materials for preparing the lithium iron phosphate positive electrode material include an iron source, a phosphorus source, a lithium source, a carbon source and the lithium source additive as claimed in claim 1 or 2; Among them, the molar ratio of the iron source, phosphorus source, lithium source and carbon source is 1:(0.8-1.2):(0.8-1.2):(0.1-0.3); the added amount of the lithium source additive accounts for 0.1-1% of the total mass of the raw materials for preparing the lithium iron phosphate positive electrode material.
6. A method for preparing the lithium iron phosphate positive electrode material according to claim 5, characterized in that: The preparation method comprises the following steps: The iron source, the phosphorus source, the lithium source and the carbon source are mixed and ground for the first time to obtain a primary mixed material; The mixed material and the lithium source additive are mixed and pre-sintered to obtain a pre-sintered material; Grinding the pre-sintered material for a second time to obtain a secondary mixed material; sintering the secondary mixed material to obtain a sintered material; The sintered material is crushed and then sieved to obtain the lithium iron phosphate positive electrode material.
7. The method for preparing a lithium iron phosphate positive electrode material according to claim 6, characterized in that: The first grinding speed is 100-500 rpm, and the first grinding time is 20-40 min; Preferably, the pre-sintering treatment is carried out in an air atmosphere; Preferably, the heating rate of the pre-sintering treatment is 1 to 10 / min, the temperature of the pre-sintering treatment is 550 to 650°C, and the time of the pre-sintering treatment is 1 to 3 hours; Preferably, the second grinding speed is 200-1000 rpm, and the second grinding time is 20-40 min; Preferably, the sintering process is carried out under a methane atmosphere; Preferably, the heating rate of the sintering process is 1 to 10 / min, the temperature of the sintering process is 650 to 750°C, and the time of the sintering process is 10 to 15 hours; Preferably, the pulverization treatment is carried out by ball milling, the ball-to-material ratio of the ball milling is (30-50):1, the rotation speed of the ball milling is 500-2000 rpm, and the ball milling time is 30-60 min; Preferably, the mesh size of the sieving is 100 to 300 meshes.
8. Use of the lithium source additive according to claim 1 or 2, or the lithium iron phosphate positive electrode material according to claim 5 in the preparation of a lithium ion battery.
9. A positive electrode plate for a lithium-ion battery, characterized in that: The lithium-ion battery positive electrode plate comprises the lithium iron phosphate positive electrode material as claimed in claim 5.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium-ion battery positive electrode sheet as claimed in claim 9.